Restriction of Toeplitz Operators on Their Reducing Subspaces - Anjian Xu; Yang Zou (Journal of Function Spaces)
We study the restrictions of analytic Toeplitz operator on its minimal reducing subspaces for the unit disc and construct their models on slit domains. Furthermore, it is shown that Tzn is similar to the sum of n copies of the Bergman shift.